Assessment of the Efficiency for some Disinfectants Against the Microorganisms Isolated From the Wards of Newborn and Premature Babies in Baghdad Teaching Hospital - hassan, Yasameen (Iraqi National Journal of Nursing Specialties, 2015)
Objective : To assess the efficiency for some disinfectants against the microorganisms isolated fromthe wards of newborn and premature babies in Educational Baghdad Hospital .Methodology :This study had done from 1\8\2014 untile 1\9\2014, we had selected three types ofdisinfectants ( Incidine , Bleach and Microbac Forte )which were used for disinfection in the wards ofnewborn babies at Educational Baghdad Hospital to assess their effect against the microorganismsisolated from these wards and study the mixed affect of these disinfectants againt samemicroorganisms .Results : The results of the present study showed that there is affect of the different concentrations ofthe used disinfectants against the microorganisms isolated from the wards of the newborn andpremature babies , also there is a synergism affect of microbac forte with sodium hypochlorite andincidine , as well as , there is an antagonism affect of sodium hypochlorite with incidine a comparisionif they used alone .Recommendation : The present study had been suggested to use the highly concentrations ofMicrobac forte , Incidine and sodium hypochlorite to sterilize the wards of newborn and prematurebabies , also the study had been suggested to use the mixed solutions of microbac forte with incidineand sodium hypochlorite to disinfect the same wards .